KEEPING IT REAL: DELIBERATE DISTORTION MECHANISM TO PRESERVE AUTHENTICITY AND DYNAMICS OF ORGANIZATIONAL COMMUNICATION MESSAGES IN AI-MEDIATED COMMUNICATION - Samsudin, Sharina; Dani, Ezzul Hilman (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The prevalence of artificial intelligence (AI) in the form of easy-to-use tools poses both opportunities and challenges towards organizational communication. The focus of this paper is on AI’s emerging role as a meta-medium, which is its capacity of transforming, generating, and integrating multiple media forms prior to their circulation through established channels. The analysis explores AI’s influence on message structure, stylistic choices, tone of voice, and the potential introduction of bias. In addition, this paper explores the theoretical implications of AI’s ever-increasing integration into the communicative environment. The discussion illustrates the potential for enhanced efficiency in message transmission while improving message clarity. However, it is hypothesized that this may also diminish message authenticity, reduce variability in daily conversations, and hinder personal expression. Drawing from McLuhan (1964) notion that “the medium is the message”, this paper integrates AI into the communication framework and proposed the Deliberate Distortion Mechanism (DDM) as a tool to enhance authenticity and individuality of AI-assisted communication. Parallels from past technological adoption suggest that mass AI adoption in the organizations is inevitable.